Pengaruh Parenting Style dan Teman Sebaya terhadap Nilai Karakter Remaja di Jorong Panta Kecamatan Matur - Febiola, Rahma Gita; Wardefi, Riza (Lembaga Yasin AlSys, 2024)
This research aims to determine the influence of parenting style and peers on the character values ​​of adolescents in Jorong Panta, Kenagarian Panta Pauh, Matur District, Agam Regency. This research uses a correlational design with a quantitative approach to analyze the relationship between two independent variables, its parenting style and peer influence, on the dependent variable, namely the formation of adolescent character. The research sample consisted of 55 teenagers aged 15 to 18 years, selected using sampling techniques. Data collection wast carried out through distributing questionnaires that measured three main dimensions: parenting style, peer influence, and adolescent character values. Data analysis was carried out using multiple linear regression to determine the magnitude of the influence of each variable on adolescent character. The results of the research show that both parental style preferences and interactions with peers have a significant influence on the character formation of teenagers in Jorong Panta.